PENGARUH CITRA MEREK DAN KUALITAS PELAYANAN TERHADAP KEPUASAN KONSUMEN COFFEE SHOP JANJI JIWA JILID 490 - Fransisca Wenas , Rienitha Mery; Ellyawati, Noor; Rahayu, Vitria Puri (Educational Studies: Conference Series, 2023)
This research aims to find out whether brand image and service quality have a significant effect on consumer satisfaction at the Janji Jiwa Jilid 490 coffee shop. The sampling technique used was non-probability sampling. Data collection carried out was a questionnaire distributed to 96 consumers, observations and interviews. The data analysis technique uses multiple linear regression analysis. The partial t test results for each variable brand image and service quality have a positive and significant effect on consumer satisfaction, then the F test results show that simultaneously brand image and service quality have a positive and significant effect on consumer satisfaction, this can be seen from the results of statistical analysis using significance value 0.000 < 0.05. Service quality is the dominant variable influencing consumer satisfaction. The R Square value is 50.8% while the remaining 49.2% is influenced by variables not examined in this research.